CT Attenuation of Pericoronary Adipose Tissue in Normal Versus Atherosclerotic Coronary Segments as Defined by Intravascular Ultrasound. Issue 5 (September 2017) - Marwan, Mohamed; Hell, Michaela; Schuhbäck, Annika; Gauss, Sören; Bittner, Daniel; Pflederer, Tobias; Achenbach, Stephan
Abstract : Background: The factors influencing genesis of atherosclerosis at specific regions within the coronary arterial system are currently uncertain. Local mechanical factors such as shear stress as well as metabolic factors, including inflammatory mediators released from epicardial fat, have been proposed. We analyzed computed tomographic (CT) attenuation of pericoronary adipose tissue in normal versus atherosclerotic coronary segments as defined by intravascular ultrasound (IVUS). Patients and Methods: We evaluated the data sets of 29 patients who were referred for invasive coronary angiography and in whom IVUS of 1 coronary vessel was performed for clinical reasons. Coronary CT angiography was performed within 24 hours from invasive coronary angiography. Computed tomographic angiography was performed using dual-source CT (Siemens Healthcare; Forchheim, Germany). A contrast-enhanced volume data set was acquired (120 kV, 400 mA/rot, collimation 2 × 64 × 0.6 mm, 60–80 mL intravenous contrast agent). Intravascular ultrasound was performed using a 40-MHz IVUS catheter (Atlantis; Boston Scientific Corporation, Natick, Mass) and motorized pullback at 0.5 mm/s. Sixty corresponding coronary artery segments within the coronary artery system were identified in both dual source computed tomography and IVUS using bifurcation points as fiducial markers. In dual source computed tomography data sets, 8 serial parallel cross sections (2-mm slice thickness) were rendered orthogonal to the center line of the coronary artery for each segment. For each cross section, pericoronary adipose tissue within a radius of 3 mm from the coronary artery and enclosed within the epicardium (excluding coronary veins and myocardium) was manually traced and mean CT attenuation values were obtained. Intravascular ultrasound was used to define coronary segments as follows: presence of predominantly fibrous atherosclerotic plaque (hyperechoic), presence of predominantly lipid-rich atherosclerotic plaque (hypoechoic), and absence of atherosclerotic plaque. Results: In IVUS, 20 coronary segments with fibrous plaque, 20 segments with lipid-rich plaque, and 20 coronary segments without plaque were identified. The mean CT attenuation of pericoronary adipose tissue for segments with any coronary atherosclerotic plaque was −34 ± 14 Hounsfield units (HU), as compared with −56 ± 16 HU for segments without plaque ( P = 0.005). The density of pericoronary fat in segments with fibrous versus lipid-rich plaque as defined by IVUS was not significantly different (−35 ± 19 HU vs −36 ± 16 HU, P = 0.8). Conclusions: Mean CT attenuation of pericoronary adipose tissue is significantly lower for normal versus atherosclerotic coronary segments. This supports a hypothesis of different types of pericoronary adipose tissue, the more metabolically active of which might exert local effects on the coronary vessels, thus contributing to atherogenesis.